Methicillin-Resistant Staphylococcus aureus Colonization among Health Care Workers in a Downtown Emergency Department in Toronto, Ontario. Issue 3 (2013) - Saito, Gregory; Thom, Jessica; Wei, Yanliang; Gnanasuntharam, Piraveina; Gnanasuntharam, Pirasanya; Kreiswirth, Nathan; Willey, Barbara; Loftus, Michelle; Varner, Catherine; Porter, Vanessa; McGeer, Allison; Borgundvaag, Bjug
Abstract : BACKGROUND: Methicillin-resistant Staphylococcus aureus (MRSA) acquired in the community, otherwise known as community-acquired MRSA, has emerged rapidly in recent years. Colonization with MRSA has been associated with an increased risk of symptomatic and serious infections and, in some settings, health care workers (HCWs) exhibit a higher prevalence of MRSA colonization. OBJECTIVE: To determine MRSA colonization in emergency department (ED) HCWs in the setting of a moderate prevalence of MRSA in skin and soft tissue infections. METHODS: The present study was conducted at a downtown ED in Toronto, Ontario. ED HCWs completed a brief questionnaire and swabs were taken from one anterior nare, one axilla and any open wounds (if present). Swabs were processed using standard laboratory techniques. RESULTS: None of the 89 staff (registered nurses [n=55], physicians [n=15], other [n=19]) were MRSA positive and 25 (28.1%) were colonized with methicillin-susceptible S aureus . CONCLUSIONS: Contrary to common belief among HCWs and previous studies documenting MRSA colonization of HCWs, MRSA colonization of this particular Canadian ED HCW cohort was very low and similar to that of the local population.